Respuesta :

Answer:

Alternative B is the correct answer.

Step-by-step explanation:

Re-arrange the quadratic equation to identify the values of a, b and c. From the equation, a=6, b=-5, c=-3. Apply the quadratic formula and replace the values of a,b and c

Answer:

Choice B is correct answer.

Step-by-step explanation:

We have given a quadratic equation.

5x = 6x²-3

6x²-3-5x = 0

6x²-5x-3 = 0

ax²+bx+c = 0 is general quadratic equation.

x =(-b±√b²-4ac) / 2a is quadratic formula to solve equation.

comparing general equation with given equation, we have

a = 6 , b = -5 and c = -3

Putting above values in formula, we have

x = (-(-5)±√(-5)²-4(6)(-3) ) / 2(6)

x = (5±√25+72) / 12

x = (5±√97) / 12 which is the answer.